Cognitive Group Therapy for Test Anxiety - Sevinc ULUSOY; Kaasim Fatih YAVUZ; Fatma Betul ESEN; Gokhan UMUT; Hasan Turan KARATEPE (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Test anxiety is a major problem that affects students academic, vocational and emotional state and several treatment strategies have been developed and applied. Cognitive behavioral therapy is one of the efficacious treatments for test anxiety, but we know little about whether cognitive or behavioral techniques (or both) are effective. The aim of this study is to assess the efficacy of cognitive techniques without behavioral interventions. The study was carried out with 38 individual who complained of test anxiety and were divided into four groups. Six 90 min sessions of cognitive group therapy is applied weekly. Test Anxiety Inventory (TAI), Beck Anxiety Inventory (BAI), State-Trait Anxiety Inventory (STAI), Ruminative Thought Style Questionnaire (RTSQ) and Automatic Thoughts Questionnaire (ATQ) were given to attendants. There was statistically significant difference between first and last evaluation of mean rank of BAI total and its cognitive and somatic subscales, ATQ and STAI-II. There was no significant difference for mean rank of STAI-I and RTSQ total scores. Statistically significant difference was found between first and last evaluation of total TAI and 3 subscales of TAI which were Others opinions, Worry about future, Worry about preparation and unspecified test anxiety. Cognitive techniques are effective for treatment of test anxiety even without behavioral interventions. However, its effect on self-related perception componenet of test anxiety and ruminative response styles is uncertain. Adding behavioral interventions to cognitive techniques may increase the efficacy of treatment for test anxiety. [JCBPR 2016; 5(1.000): 28-37]